2010
DOI: 10.1111/j.1468-1293.2010.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV and risk of venous thromboembolism: a Danish nationwide population-based cohort study

Abstract: ObjectiveThe association between HIV infection and the risk of venous thromboembolism (VTE) is controversial. We examined the risk of VTE in HIV-infected individuals compared with the general population and estimated the impact of low CD4 cell count, highly active antiretroviral therapy (HAART) and injecting drug use (IDU). MethodsWe identified 4333 Danish HIV-infected patients from the Danish HIV Cohort Study and a population-based age-and gender-matched comparison cohort of 43 330 individuals. VTE diagnoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 46 publications
1
79
0
1
Order By: Relevance
“…Whereas the clinical implications of these findings in BALF require further study, HIV infection is strongly linked to increased risk of developing pulmonary hypertension (regardless of ART status) (39) and venous thromboembolism (32).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the clinical implications of these findings in BALF require further study, HIV infection is strongly linked to increased risk of developing pulmonary hypertension (regardless of ART status) (39) and venous thromboembolism (32).…”
Section: Discussionmentioning
confidence: 99%
“…Protease inhibitors based therapy promotes thrombosis by inducing platelets and endothelial dysfunction [13]. Nonetheless it is still unclear whether non-protease inhibitors are prothrombotic or not [11,14]. Our patient is on reverse transcriptase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Inspite of the fact that the absolute risk of thrombosis in patients who are not on combined antiretroviral therapy is almost 6 folds in comparison to healthy population of the same age, there is an additional risk of thrombosis in patients on HAART [10,11]. The prothrombotic effect of HAART is reported to be more common in combinations including protease inhibitors (PIs) [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…This associa tion has been definitely established in a Danish population based study. 3 In Box 1 of our Review, 2 we identified that infectious diseases are associated with an increased risk of VTE, 4 but avoided detailing particu lar infectious agents. For example, acute Cytomegalovirus infection, which is far more common than HIV infection, doubles the risk of VTE.…”
Section: Correspondencementioning
confidence: 99%
“…Therefore, the statement that patients who are infected with HIV and carry one of the common mild thrombophilia abnormal ities should be considered at higher risk of VTE than individuals who are not infected with HIV remains speculative. Considering that combined antiretroviral therapy might increase the risk of VTE, 3 we prefer not to cause unwarranted alarm in the 6-8% of patients with HIV who carry hetero zygous factor V Leiden or the prothrombin mutation with assumptions that are not evidence based. …”
Section: Ida Martinelli Valerio De Stefano and Pier Mannuccio Mannuccimentioning
confidence: 99%